An X-Lin ked Haplotype of Neandertal Origin Is Present Among All Non-African Populations - (:unkn) unknown (My University, 2011)
Recent work on the Neandertal genome has raised the possibility of admixture between Neandertals and the expanding population of Homo sapiens who left Africa between 80 and 50 Kya (thousand years ago) to colonize the rest of the world. Here, we provide evidence of a notable presence (9% overall) of a Neandertal-derived X chromosome segment among all contemporary human populations outside Africa. Our analysis of 6,092 X-chromosomes from all inhabited continents supports earlier contentions that a mosaic of lineages of different time depths and different geographic provenance could have contributed to the genetic constitution of modern humans. It indicates a very early admixture between expanding African migrants and Neandertals prior to or very early on the route of the out-of-Africa expansion that led to the successful colonization of the planet.
Keywords: African Research